Automated Stand-Alone Bot for Intruder Detection - Butale, Mohit (INTERANTIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2024)
The Automated Standalone Bot for Intruder Detection System represents a cutting-edge approach to bolstering security measures through the deployment of an intelligent surveillance system. By harnessing sophisticated computer vision techniques, this system is capable of vigilantly monitoring its surroundings and swiftly identifying potential security threats with remarkable accuracy. Through continuous real-time analysis of video feeds and the application of advanced image processing algorithms, the bot can promptly detect any unauthorized individuals or suspicious activities within its designated area of coverage. Upon detecting a potential intruder, the system initiates an immediate response protocol, which may include activating alarms, notifying security personnel, or implementing deterrent measures to deter any further intrusion attempts. What sets this system apart is its ability to continually refine its intruder detection capabilities over time, leveraging machine learning algorithms to adapt to evolving threats and minimize false positives. Moreover, the system demonstrates remarkable discernment by distinguishing between human subjects, animals, and other objects, thereby reducing the occurrence of false alarms and enhancing its overall reliability. This comprehensive approach not only fortifies security measures but also instills a greater sense of confidence in the system's ability to safeguard the premises effectively. Key Words: Automated Standalone Bot, Intruder Detection System, Security Measures, Intelligent System, Computer Vision Techniques, Surveillance, Real-time Analysis, Video Feeds, Image Processing Algorithms, Swift Detection, Unauthorized Individuals, Suspicious Activities, Response Protocol, Alarms, Notification, Deterrent Measures, Machine Learning Algorithms, Adaptation, False Positives, Reliability, Human Subjects, Animals, False Alarms, Premises Security